SPIRITUALITAS ISLAM DALAM SULUK WUJIL KARYA SUNAN BONANG BERDASARKAN KAJIAN SEMIOTIK - Zalikha Zalikha; Dadan Rusmana (Haluan Sastra Budaya, 2023)
Suluk Wujil is a well-known early Javanese Islamic literary work that focuses on spiritual pursuits and teachings. Wujil, a convert seeking the ultimate truth, is a symbolic person who carries crucial Sufistic teachings as well as the revelation of socio-religious discourse at the dawn of Islam in Java. This article uses three steps of semiotic reading to disclose the content of Suluk Wujil: narrative framework, primary sign discovery, and syntagmatic and paradigmatic analysis. First, the Suluk Wujils narrative plan arose from Wujil's complaint that after ten years of spiritual study in Bonang, he had failed to enter The Ultimate Truth. The statement "Arriving in Mecca" at the end of the book is the second key sign of Suluk Wujil. This term emphasizes Suluk Wujil's spiritual qualities in relation to the spiritual path toward the reality of Islamic mysticism. Third, the paradigmatic analysis reveals that multiple parallel and contrary signs exist at the same moment. The combination of various signs forms a synthesis that leads to a deeper comprehension of the meaning of these indicators. Syntagmatic analysis leads to a better comprehension of indications that are diametrically opposed but complementary.